Hukum Islam Pada Masa Awal Masuknya Islam Ke Nusantara - Usqo, Hanafi Urwatil; Fuad, Zainul; Sarumpaet, M. Idris (CV. ITTC INDONESIA, 2024)
In fact, Islam Nusantara is not something new. The bolding of the word